Effect of Curing Method on Concrete with Palm Oil Fuel Ash as a Cement Replacement - Elleithy, Wael; Chee Fung, Chin; Jaganathan, Jayaprakash; Leong Lau, Teck; Parvez Anwar, Mohammed (International Journal of Engineering and Technology, 2018)
In this paper, the effect of different curing methods on the strength of concrete with palm oil fuel ash as a cement replacement is investigated. An experimental program was carried out to study the effect of five different curing methods, i.e., water curing (WC), air curing (AC), plastic-wrapped curing (PC), oven and water curing (OWC), and oven and air curing (OAC), on the compressive and flexural strengths of palm oil fuel ash concrete (POFA20), where 20% of the cement was replaced by palm oil fuel ash. The results obtained from this investigation showed that POFA20-WC has the highest compressive and flexural strength, whilst POFA20-AC has the lowest at the age of 28 days. Both of the POFA20-OWC and POFA20-OAC have the highest compressive and flexural strength at the age of 3 days. The results emphasize the positive effect of oven curing procedure to achieve high compressive and flexural strength at early stage. However, the rate of hydration started to decrease at later stages, which leads to much lower rate of gaining strength in POFA20-OWC and POFA20-OAC. Water curing method is thus recommended in the construction industry except for extraordinary requirements and/or circumstances.Â Â Â